Correlation between Oxidative Stress and Thyroid Function in Patients with Nephrotic Syndrome - Sangita U. Sawant; Subhash Chandran; Alan F. Almeida; M. G. R. Rajan (International Journal of Nephrology)
Background. The present study is to look for a correlation between oxidative stress and thyroid function in patients with the nephrotic syndrome in the remission phase as well as in a persistent proteinuric state. Introduction. Nephrotic syndrome is a form of chronic kidney disease due to which blood loses protein through the urine. We wanted to know if there was an increased loss of thyroid hormones in urine affecting thyroid function. Methods. 60 patients with nephrotic syndrome and 20 healthy non-proteinuric individuals as control subjects were enrolled in the study. We measured their serum tri-iodothyronine, thyroxine and thyroid-stimulating hormone. Estimation of lipid peroxidation (LPx) catalase, superoxide dismutase (SOD), and Glutathione peroxidase (GPx) were carried out by standard methods. Results. TSH was elevated in the nephrotic patients compared to controls, while TT4 and TT3 were significantly lower in the patients than in controls. Lipid Peroxidation and GPx were significantly higher in the nephrotic syndrome patients than in the controls, while SOD and catalase were significantly lower than in patients than in the control subjects. Conclusion. Nephrotic patients can lose significant amounts of thyroid hormones along with protein in urine, which can affect thyroid status, but this is reversible on remission.